THE CONTRIBUTION OF AN UNKNOWN PERSON TO THE FORMATION OF THE KYRGYZ STATEHOOD - Mukanbetova R. B.; Ibraev Ch. T. (Vestnik Issyk-Kulʹskogo universiteta)
In this article, the authors show a name unknown in wide circles, as well as, in principle, thousands of other people who participated in the formation of the Kyrgyz statehood in the 20th and 30th centuries. S. Ismailov, who was born at the beginning of the 20th century, learned all the hardships and vicissitudes of fate from a young age. He lost his parents early, who came from sharecropping peasants. Since the age of 8, he has been working as a hired handyman for the kulaks, doing a variety of hard work. During the uprising of 1916, he and his relatives made an exodus to China. After the establishment of Soviet power in Kyrgyzstan, he returned and received education at the Soviet party school. He works in various responsible party positions. Ismailov made his contribution to the formation and development of the Kyrgyz SSR. In 1938, he was arrested, accused of belonging to the Social Turanian Party, as well as a number of other fictitious charges - espionage, nationalism, etc. In the same year, he was sentenced to death by firing squad. In 1958, all charges were dropped against S. Ismailov and he was rehabilitated posthumously.